Systematic, synonymic and biogeographical list of ptyctimous mites (Acari, Oribatida) in the world (1799–2022) - Niedbała, Wojciech; Liu, Dong (Zootaxa, 2023)
The primitive ptyctimous mites are one of the most important groups of oribatid mites (Acari), with almost cosmopolitan distribution, except for the Arctic and the Antarctic regions. These mites occur especially in places where there is decaying organic matter. In this study, a detailed catalogue of all known ptyctimous mite species in the world is presented. The catalogue provides information about the zoogeographical distribution of each species, discusses important nomenclatural issues and addresses some remarks. Besides this, it also contains useful data on known juvenile instars of 47 species. The catalogue also presents a classification of the higher taxa of eight families, four subfamilies, 42 genera, 15 subgenera, the taxonomic characteristics and the information about the zoogeographical distribution of 1458 valid known species from all over the world. Among them, 231 species and one genus are enumerated as synonyms, nine homonyms, one rejected name, one genus inquirenda, 41 species inquirendae, four subspecies inquirendae, one genus incertae sedis, 39 species incertae sedis, 12 species nomina nuda, two species mistakenly identified, one species without the author’s name, and one non-ptyctimous mite species are included in the catalogue. Furthermore, the DNA sequence data of 53 ptyctimous species (belonging to eight families, 15 genera) can be found in the GenBank. Finally, the attached appendix contains important corrections referring to the published monographs published by the first author, and a list of new species described after the publication of these monographs. SEM photos of some typical ptyctimous mites showing their diversity are attached.